1996
DOI: 10.1038/bjc.1996.502
|View full text |Cite
|
Sign up to set email alerts
|

Continuous infusion or subcutaneous injection of granulocyte-macrophage colony-stimulating factor: increased efficacy and reduced toxicity when given subcutaneously

Abstract: Summary Granulocyte-macrophage colony-stimulating factor (GM-CSF) is a haematopoietic growth factor with a wide variety of applications in the clinic. In early phase I studies the continuous intravenous (c.i.) route of administration was often used. Later it was shown that subcutaneous (s.c.) administration was also effective. The optimal route of administration remains, however, poorly defined, and no studies have made a direct comparison between these two routes of administration. We treated patients with ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…GM-CSF 250 µg/m 2 /day was administered from days 2-11, in the first four patients as a continuous i.v. infusion and in the following 38 patients s.c. [17]. Initially, some patients received fewer than six cycles.…”
Section: Treatmentmentioning
confidence: 99%
“…GM-CSF 250 µg/m 2 /day was administered from days 2-11, in the first four patients as a continuous i.v. infusion and in the following 38 patients s.c. [17]. Initially, some patients received fewer than six cycles.…”
Section: Treatmentmentioning
confidence: 99%
“…Although package inserts for CSFs consider intravenous and subcutaneous administration to be equipotent, adult data have found that 2-4 times dosing is required to achieve equivalent effect when either G-CSF or GM-CSF is given intravenous as compared to subcutaneous (Eguchi et al 1990 ;Kaneko et al 1991 ;Stute et al 1995 ;Honkoop et al 1996 ). Adult guidelines all suggest subcutaneous administration for CSFs ESMO 2007 ;Aapro et al 2011 ).…”
Section: Route Of Administrationmentioning
confidence: 99%
“…Toxicity may also be schedule-dependent, as continuous intravenous infusion of sargramostim causes more adverse effects than subcutaneous injection. [89] There has been some concern that GM-CSF may contribute to lower platelet counts, [27,28,90] possibly by causing stimulation of platelet-consuming Kupffer cells in the liver. [91] However, because other randomised paediatric studies [26,92] have reported increased platelet counts and the need for fewer platelet transfusions when GM-CSF is used as primary prophylaxis, firm conclusions are difficult to reach.…”
Section: Toxicity Spectrum Of G-csf and Gm-csfmentioning
confidence: 99%